Taá¹bÄ«q NamÅ«zaj at-TaÊ¿lÄ«m bi al-TakhmÄ«n li IstÄ«Ê¿Äb al-MufradÄt al-Lugah al-Ê¿Arabiyyah laday TalamÄ«Å¼ Rauá¸ah al-Aá¹fÄl â€œNÅ«rul Husnayainâ€ bi Bukittinggi - Sari, Indah (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
This research is about applying the guessing teaching model to comprehend the vocabulary of the Kindergarten pupils "Nurul Husnayain, Bukittinggi. The problems in this research mean that some understand the lesson, and some do not. While studying, some are dumbfounded when they hear the teacher. When reading the lessons in singing style, the pronunciation is read long but short, and vice versa. The type of research used is qualitative descriptive research. The research tools are interviews and observation. The method of data analysis used in this research is the analysis of the Millis and Huberman model, which means summarizing and exposing the data. As for the research results, there is an application of a guessing teaching model to comprehend vocabulary among pupils of Kindergarten "Nurul Husnayaian" Bukitinggi. Teaching with this model is effective to be applied in Kindergarten "TAUD NUHA." From the research results, students can answer the guesswork from the characteristics conferred by the teacher.Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¹Ù† ØªØ·Ø¨ÙŠÙ‚ Ù†Ù…ÙˆØ°Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„ØªØ®Ù…ÙŠÙ† Ù„Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ ØªÙ„Ø§Ù…ÙŠØ° Ø±ÙˆØ¶Ø© Ø§Ù„Ø£Ø·ÙØ§Ù„ "Ù†ÙˆØ± Ø§Ù„ØØ³Ù†ÙŠÙŠÙ†" Ø¨Ø¨ÙˆÙƒÙŠØª ØªÙ†Ø¬ÙŠ. Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙŠØ¹Ù†ÙŠ ÙŠÙÙ‡Ù… Ø§Ù„Ø¨Ø¹Ø¶ Ø§Ù„Ø¯Ø±Ø³ØŒ ÙˆØ§Ù„Ø¨Ø¹Ø¶ Ø§Ù„Ø¢Ø®Ø± Ù„Ø§ Ø£Ø«Ù†Ø§Ø¡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø©ØŒ ÙŠØµØ§Ø¨ Ø§Ù„Ø¨Ø¹Ø¶ Ø¨Ø§Ù„Ø°Ù‡ÙˆÙ„ Ø¹Ù†Ø¯ Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ Ø¥Ù„Ù‰ Ø§Ù„Ù…Ø¹Ù„Ù…Ø©.Â Â  Ø¹Ù†Ø¯ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ø¯Ø±ÙˆØ³ Ø¨Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØºÙ†Ø§Ø¡ØŒ ÙŠÙ‚Ø±Ø£ Ø§Ù„Ù†Ø·Ù‚ Ø·ÙˆÙŠÙ„Ø§Ù‹ ÙˆÙ„ÙƒÙ† Ù…Ø®ØªØµØ±Ù‹Ø§ ÙˆØ§Ù„Ø¹ÙƒØ³ ØµØÙŠØ. Ø£Ù…Ø§ Ù†ÙˆØ¹ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù… Ù‡Ùˆ Ø¨ØØ« Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ÙƒÙŠÙÙŠ. ÙˆØ£Ø¯ÙˆØ§Øª Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ù…Ù‚Ø§Ø¨Ù„Ø© ÙˆÙ…Ù„Ø§ØØ¸Ø©. ÙˆØ£Ø³Ù„ÙˆØ¨ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ø°ÙŠ ØªØ³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ«Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ ØªØÙ„ÙŠÙ„ Ù†Ù…ÙˆØ°Ø¬ Ù…ÙŠÙ„ÙŠØ³ ÙˆÙ‡ÙˆØ¨ÙŠØ±Ù…Ø§Ù† ÙŠØ¹Ù†ÙŠ ØªÙ„Ø®ÙŠØµ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆØªØ¹Ø±ÙŠØ¶Ù‡Ø§. ÙˆØ£Ù…Ø§ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« ÙÙ‡ÙŠ ØªÙˆØ¬Ø¯ ØªØ·Ø¨ÙŠÙ‚ Ù†Ù…ÙˆØ°Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„ØªØ®Ù…ÙŠÙ† Ù„Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ ØªÙ„Ø§Ù…ÙŠØ° Ø±ÙˆØ¶Ø© Ø§Ù„Ø£Ø·ÙØ§Ù„ "Ù†ÙˆØ± Ø§Ù„ØØ³Ù†ÙŠÙŠÙ†" Ø¨Ø¨ÙˆÙƒÙŠØª ØªÙ†Ø¬ÙŠØŒ ØªÙ‚ÙˆÙ… Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¨ØªØ¯Ø±ÙŠØ³ Ù†Ù…ÙˆØ°Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„ØªØ®Ù…ÙŠÙ† Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙŠØªØ¹Ù„Ù… Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° ÙÙŠÙ‡ Ù…ÙØ±Ø¯Ø§Øª Ø£Ø¹Ø¶Ø§Ø¡ Ø§Ù„Ø¬Ø³Ù…. Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù‡Ø°Ø§ Ø§Ù„Ù†Ù…ÙˆØ°Ø¬ ÙØ¹Ø§Ù„ Ù„ÙŠØªÙ… ØªØ·Ø¨ÙŠÙ‚Ù‡ ÙÙŠ Ø±ÙˆØ¶Ø© Ø§Ù„Ø£Ø·ÙØ§Ù„Â  "ØªÙˆØ¯ Ù†Ù‡Ù‰" ÙˆÙ…Ù† Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ«ØŒ ÙŠÙ…ÙƒÙ† Ù„Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø© Ø¹Ù„Ù‰ Ø§Ù„ØªØ®Ù…ÙŠÙ† Ù…Ù† Ø§Ù„Ø®ØµØ§Ø¦Øµ Ø§Ù„ØªÙŠ ÙŠÙ†Ù‚Ù„Ù‡Ø§ Ø§Ù„Ù…Ø¹Ù„Ù….